Carbon-grid-derived multi-layer composite bipolar plate for vanadium battery and preparation method of carbon-grid-derived multi-layer composite bipolar plate

By using carbon fiber material in composite bipolar plates for etching treatment and combining multi-layer conductive support layer modification technology, the problems of conductivity and mechanical strength are solved, the performance of bipolar plates is significantly improved, and its in vanadium battery is enhanced application capability.

CN119230862AActive Publication Date: 2024-12-31HANGZHOU DEHAI AIKE ENERGY TECH CO LTD

Patent Information

Application Number
CN202411756856.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2024-12-31
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

The existing composite bipolar plates have shortcomings in improving conductivity and mechanical strength, especially when the graphite content is high, the airtightness and mechanical strength decrease, and when the resin content is high, the conductivity decreases, making it difficult to take into account both the conductive properties and mechanical strength.

Method used

Using carbon fiber material as the substrate, the surface roughness and active surface area are improved through etching treatment, combined with the modification technology of multi-layer conductive support layer, the mechanical interlocking effect of carbon fiber and conductive fillers and resins is used to form a strong interface bonding force, enhance conductivity and Mechanical strength.

Benefits of technology

It significantly improves the conductivity and mechanical strength of the composite bipolar plate, enhances corrosion resistance and durability, reduces the internal resistance of the battery, and improves the overall efficiency of the vanadium battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230862A_ABST
    Figure CN119230862A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of all-vanadium redox flow batteries, and discloses a carbon grid derived multi-layer composite bipolar plate for a vanadium battery and a preparation method of the carbon grid derived multi-layer composite bipolar plate for the vanadium battery. The preparation method comprises the following steps: brushing a mixed slurry 1 prepared from a conductive filler, a binder and the like onto the surface to obtain preliminarily modified carbon fibers, then brushing a mixed slurry 2 prepared from oxide nanoparticles, conductive macromolecules and the like onto two surfaces of the preliminarily modified carbon fibers, drying, and repeating the two brushing and drying steps to obtain multi-layer conductive support layer modified carbon fibers; graphite paper is attached to the obtained carbon fibers, and then hot pressing treatment is performed to obtain the carbon conductive grid derived multi-layer composite bipolar plate. According to the prepared multi-layer composite bipolar plate, the etched carbon fiber is used as a substrate, beneficial mechanical strength and conductive grids are provided through stacking of the multiple layers of conductive coatings, the stability and conductivity of the bipolar plate are effectively improved, and therefore the efficiency of a vanadium battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of bipolar plates for all-vanadium liquid flow batteries, and in particular relates to a multi-layer composite bipolar plate derived from a carbon grid for a vanadium battery and a preparation method thereof. Background Art

[0002] All-vanadium liquid flow battery is the most technologically mature type of liquid flow battery currently available. It has the characteristics of high safety, high cycle life, and strong scalability. It is a very promising large-scale energy storage technology that provides a guarantee for the grid-connected application of a high proportion of renewable energy.

[0003] Bipolar plates are important components in all-vanadium flow batteries. They connect the positive and negative electrodes of adjacent cells in series, conduct the internal circuit, block the electrolyte on both sides, and support the positive and negative electrodes. At present, bipolar plates can be divided into metal bipolar plates, graphite bipolar plates, and composite bipolar plates according to the composition materials. Among them, metal bipolar plates have certain advantages in mechanical properties and good conductivity, but there is a more serious electrochemical corrosion phenomenon; graphite bipolar plates have high conductivity, low density and good corrosion resistance, but lack mechanical strength and are prone to brittle fracture.

[0004] Composite bipolar plates are made of two or more materials, usually made of conductive fillers and resins through injection molding. However, when the graphite content is high, the air tightness and mechanical strength of the bipolar plate decrease; and when the resin content is high, the conductivity of the bipolar plate decreases, and it is difficult to balance the conductivity and mechanical strength. Therefore, the development of composite bipolar plates with high conductivity and high mechanical strength is important for improving the performance of all-vanadium liquid flow batteries. Summary of the invention

[0005] The purpose of the present invention is to provide a multilayer composite bipolar plate derived from a carbon grid for vanadium batteries and a preparation method thereof, which realizes a dual improvement in the conductivity and mechanical strength of the composite bipolar plate based on the high conductivity, strong support and strong mechanical strength of the carbon grid and slurry.

[0006] The technical solution of the present invention is: Step S1: After washing 2-8 parts by mass of carbon fiber material with acetone, ethanol and deionized water in sequence, placing it in 200-400 parts by mass of etching solution and adding 0.2-0.6 parts by mass of reinforcing agent and 0.5-1.2 parts by mass of stabilizer thereto, the carbon fiber material is fully dispersed, and then the carbon fiber material is transferred to an oven for drying treatment, and the dried carbon fiber material is transferred to a tubular furnace, and subjected to staged temperature increase heat treatment under the protection of an inert gas, and after naturally cooling to room temperature, the obtained carbon fiber material is cleaned with a chemical cleaning agent and then dried to obtain an etched carbon fiber material; Step S2: Disperse the conductive filler, binder and excipient in an organic solvent to prepare a mixed slurry 1, and apply the mixed slurry 1 to both sides of the etched carbon fiber material with a brushing amount of 0.2-0.5 g / cm 2 and transferring it to a drying oven for preliminary drying treatment to obtain a preliminary modified carbon fiber material; Step S3: Disperse oxide nanoparticles, conductive polymer, phthalate coupling agent and dispersant in an aqueous polyurethane solution with a solid content of 20%-40% to prepare a mixed slurry 2, and then apply the mixed slurry 2 to both sides of the preliminary modified carbon fiber material with a brushing amount of 0.1-0.6 g / cm 2 , and perform secondary drying treatment; repeat the steps of "brushing mixed slurry 1-preliminary drying-brushing mixed slurry 2-secondary drying" 6-10 times to obtain a multi-layer conductive support layer modified carbon fiber material; Step S4: Brush polyvinyl alcohol acetal glue onto both sides of the multi-layer conductive support layer modified carbon fiber material, and then attach graphite paper on both sides to obtain a "graphite paper-multi-layer conductive support layer modified carbon fiber material-graphite paper" structure, transfer it to a hot press, set the temperature and pressure, and perform hot pressing treatment to obtain a carbon grid-derived multi-layer composite bipolar plate.

[0007] Preferably, in step S1, the carbon fiber material is one of carbon paper, carbon cloth, carbon felt and graphite felt; the etching solution is one of chloride solution, sulfate solution, nitrate solution and acetate solution of nickel, copper, cobalt and iron, as an illustrative example, it can be one of nickel chloride solution, copper sulfate solution, ferric nitrate solution and cobalt acetate solution, and the molar concentration of the etching solution is 0.3-2 mol / L; the enhancer is one of calcium hydrogen phosphate, calcium carbonate, calcium pyrophosphate, aluminum hydroxide and silicon dioxide; the stabilizer is one of dibenzothiophene, 1-isopropylpyrrolidine, octahydroisobenzofuran, 2,3-dimethylbenzofuran and 2-amino-3-bromothiophene.

[0008] Preferably, in step S1, the drying heat treatment temperature is 80-120°C, the time is 8-10 h, and the inert gas is one of nitrogen, argon and helium; the staged heating heat treatment process is: first heat treatment at 300-500°C for 2-4 h, and then heat treatment at 850-1000°C for 1-3 h.

[0009] Preferably, the chemical cleaning agent in step S1 is one of citric acid solution, sulfuric acid solution, tartaric acid solution, ascorbic acid and nitric acid solution, and the concentration of the chemical cleaning agent is 0.5-3 mol / L.

[0010] Preferably, in step S2, the conductive filler is one of conductive carbon black, graphene and carbon nanotubes; the binder is one of epoxy resin, polyimide resin, polyurethane resin and acrylic resin; the excipient is one of magnesium aluminum silicate compound powder, diethanolamine chloride, polyethylene glycol and coconut diethanolamide; the organic solvent is one of N,N-dimethylacetamide solution, xylene solution, ethyl acetate solution and ethylene glycol solution; the mass ratio of the conductive filler, the binder, the excipient and the organic solvent is (20-40): (2-5): (0.5-1.5): (80-150).

[0011] Preferably, the preliminary drying treatment temperature in step S2 is 150-200° C. and the time is 10-20 min.

[0012] Preferably, the oxide nanoparticles in step S3 are one of indium tin oxide, antimony tin oxide, cesium tungsten oxide and aluminum-doped zinc oxide; the conductive polymer is one of polyaniline, polypyrrole and poly (3,4-ethylenedioxythiophene); the phthalate coupling agent is one of isopropyl trioleyl titanate, isopropyl tri (dodecylbenzenesulfonyl) titanate, tristearyl titanate isopropyl ester, isopropyl tri (dioctyl pyrophosphate) titanate and neoalkoxy tri (p-aminophenoxy) titanate; the dispersant is one of polyacrylic acid, dimethyl sulfonic acid, p-toluene phosphoric acid and diamyl sulfate; the mass ratio of the oxide nanoparticles, the conductive polymer, the phthalate coupling agent, the dispersant and the aqueous polyurethane solution with a solid content of 20%-40% is (8-15): (20-40): (2-5): (0.5-3): (200-400).

[0013] Preferably, the secondary drying treatment temperature in step S3 is 300-500° C. and the time is 3-10 min.

[0014] Preferably, in step S4, the mass ratio of polyvinyl alcohol acetal glue, graphite paper and multi-layer conductive support layer modified carbon fiber material is (2-5): (0.2-1): (50-80), the hot press temperature is set to 140-200°C, the pressure is set to 5-10 MPa, the hot pressing time is 3-8 min, and the number of hot pressing times is 3-7 times.

[0015] A multi-layer composite bipolar plate derived from a carbon grid for a vanadium battery is prepared by using the above-mentioned method for preparing a multi-layer composite bipolar plate derived from a carbon grid for a vanadium battery.

[0016] The beneficial effects of the present invention include at least: The present invention uses carbon fiber material as the substrate and utilizes the excellent high strength and low density of the carbon grid itself to reduce the weight while maintaining the stability and durability of the composite bipolar plate. The excellent corrosion resistance and acid and alkali resistance also ensure its good applicability in vanadium batteries. At the same time, the strong conductivity provided by the carbon fiber material grid is also conducive to strengthening the internal electronic conduction of the composite bipolar plate and improving the conductivity of the bipolar plate.

[0017] By etching the carbon fiber material body, the surface roughness and active surface area of ​​the carbon fiber material can be effectively improved, and the mechanical interlocking effect between the carbon fiber material and the conductive filler and resin can be enhanced, thereby enhancing the bonding strength between the two, forming a stronger interface bonding force, and improving the mechanical strength, stability and conductivity of the composite bipolar plate.

[0018] The repeated stacking of multiple conductive support layers is conducive to providing a fast conductive grid, accelerating the electron transfer process inside the bipolar plate, and significantly increasing the conductive area and conductive channel of the bipolar plate, thereby reducing the internal resistance and planning phenomenon of the battery and improving the battery efficiency; the multiple conductive layers form a mutually supporting and protective structure, which effectively resists the erosion and damage of the bipolar plate by the external environment, improves the tensile resistance of the bipolar plate, and enhances the corrosion resistance and durability of the bipolar plate, thereby improving the efficiency of the vanadium battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 A schematic diagram of a method for preparing a multi-layer composite bipolar plate derived from a carbon grid for a vanadium battery according to the present invention; Figure 2 This is a schematic diagram of the structure of a multi-layer composite bipolar plate derived from a carbon grid for a vanadium battery of the present invention. DETAILED DESCRIPTION

[0020] See also Figure 1 and Figure 2 , a method for preparing a multilayer composite bipolar plate derived from a carbon grid for a vanadium battery and a schematic diagram of the structure, mainly comprising the following steps and components: Step S1: After washing 2-8 parts by weight of carbon fiber material with acetone, ethanol and deionized water in turn, placing it in 200-400 parts by weight of etching solution and adding 0.2-0.6 parts by weight of reinforcing agent and 0.5-1.2 parts by weight of stabilizer thereto for full dispersion, then transferring the carbon fiber material to an oven for drying, transferring the dried carbon fiber material to a tubular furnace, performing a staged temperature increase heat treatment under the protection of an inert gas, and after cooling it naturally to room temperature, washing the obtained carbon fiber material with a chemical cleaning agent and drying it to obtain an etched carbon fiber material; the carbon fiber material is one of carbon paper, carbon cloth, carbon felt and graphite felt; the etching solution is one of a chloride solution, a sulfate solution, a nitrate solution and an acetate solution of nickel, copper, cobalt and iron, and as an illustrative example, it can be one of a nickel chloride solution, a copper sulfate solution, a ferric nitrate solution and a cobalt acetate solution, and the molar concentration of the etching solution is 0.3-2 mol / L; the reinforcing agent is one of calcium hydrogen phosphate, calcium carbonate, calcium pyrophosphate, aluminum hydroxide and silicon dioxide; the stabilizer is one of dibenzothiophene, 1-isopropylpyrrolidine, octahydroisobenzofuran, 2,3-dimethylbenzofuran and 2-amino-3-bromothiophene; the mass ratio of carbon fiber material, reinforcing agent, stabilizer and etching solution is (2-8): (0.2-0.6): (0.5-1.2): (200-400); the drying heat treatment temperature is 80-120℃, the time is 8-10 h, and the inert gas is one of nitrogen, argon and helium; the staged heating heat treatment process is: first heat treatment at 300-500℃ for 2-4 h, then heat treatment at 850-1000℃ for 1-3 h; the chemical cleaning agent is one of citric acid solution, sulfuric acid solution, tartaric acid solution, ascorbic acid and nitric acid solution, and the concentration of the chemical cleaning agent is 0.5-3 mol / L.

[0021] Step S2: Disperse the conductive filler, binder and excipient in an organic solvent to prepare a mixed slurry 1, and apply the mixed slurry 1 to both sides of the etched carbon fiber material with a brushing amount of 0.2-0.5 g / cm 2 and transfer it to a drying oven for preliminary drying treatment to obtain a preliminary modified carbon fiber material; the conductive filler is one of conductive carbon black, graphene and carbon nanotubes; the binder is one of epoxy resin, polyimide resin, polyurethane resin and acrylic resin; the excipient is one of magnesium aluminum silicate compound powder, diethanolamine chloride, polyethylene glycol and coconut diethanolamide; the organic solvent is one of N,N-dimethylacetamide solution, xylene solution, ethyl acetate solution and ethylene glycol solution; the mass ratio of the conductive filler, the binder, the excipient and the organic solvent is (20-40): (2-5): (0.5-1.5): (80-150); the preliminary drying treatment temperature is 150-200℃, and the time is 10-20 min.

[0022] Step S3: Disperse oxide nanoparticles, conductive polymer, phthalate coupling agent and dispersant in an aqueous polyurethane solution with a solid content of 20%-40% to prepare a mixed slurry 2, and then apply the mixed slurry 2 to both sides of the preliminary modified carbon fiber material with a brushing amount of 0.1-0.6 g / cm 2 , and perform secondary drying treatment; repeat the steps of "brushing mixed slurry 1-preliminary drying-brushing mixed slurry 2-secondary drying" for 6-10 times to obtain a multi-layer conductive support layer modified carbon fiber material; the oxide nanoparticles are one of indium tin oxide, antimony tin oxide, cesium tungsten oxide and aluminum-doped zinc oxide; the conductive polymer is one of polyaniline, polypyrrole and poly (3,4-ethylenedioxythiophene); the phthalate coupling agent is isopropyl trioleyl titanate, isopropyl tri (dodecylbenzenesulfonyl) titanate, tristearyl titanate isopropyl, isopropyl One of tri(dioctylpyrophosphate) titanate and neoalkoxy tri(p-aminophenoxy) titanate; the dispersant is one of polyacrylic acid, dimethylsulfonic acid, p-toluenephosphoric acid and diamyl sulfate; the mass ratio of oxide nanoparticles, conductive polymer, phthalate coupling agent, dispersant and aqueous polyurethane solution with a solid content of 20%-40% is (8-15):(20-40):(2-5):(0.5-3):(200-400); the secondary drying treatment temperature is 300-500℃ and the time is 3-10 min.

[0023] Step S4: Brush polyvinyl alcohol acetal glue onto both sides of the multi-layer conductive support layer modified carbon fiber material, and then attach graphite paper on both sides to obtain a "graphite paper-multi-layer conductive support layer modified carbon fiber material-graphite paper" structure, transfer it to a hot press, set the temperature and pressure, and perform hot pressing treatment to obtain a carbon grid-derived multi-layer composite bipolar plate; the mass ratio of polyvinyl alcohol acetal glue, graphite paper and composite slurry modified carbon fiber material is (2-5): (0.2-1): (50-80), the hot press temperature is set to 140-200°C, the pressure is set to 5-10 MPa, the hot pressing time is 3-8 min, and the number of hot pressing times is 3-7 times.

[0024] Embodiment 1 This embodiment includes the following steps: Step S1: After washing 2 parts by mass of graphite felt with acetone, ethanol and deionized water in sequence, the graphite felt is placed in 400 parts by mass of 2 mol / L ferric nitrate etching solution, and 0.6 parts by mass of calcium carbonate and 1.2 parts by mass of octahydroisobenzofuran are added thereto for full dispersion, and then the graphite felt is transferred to an oven and dried at 120°C for 8 h, and the dried graphite felt is transferred to a tubular furnace for staged temperature-raising heat treatment under nitrogen protection, i.e., firstly heat-treated at 500°C for 2 h, and then heated to 850°C for 3 h, and after naturally cooling to room temperature, the obtained graphite felt is washed with 1.5 mol / L sulfuric acid solution and then dried to obtain etched graphite felt; Step S2: Disperse graphene, polyurethane resin and polyethylene glycol in a xylene solution to prepare a mixed slurry 1, wherein the mass ratio of graphene, polyurethane resin, polyethylene glycol and xylene solution is 40:5:0.5:150, and apply the mixed slurry 1 to both sides of the etched graphite felt by brushing, and the brushing amount is 0.5 g / cm 2 and transferred it to a drying oven and dried at 200°C for 10 min for preliminary drying treatment to obtain preliminary modified graphite felt; Step S3: Antimony tin oxide nanoparticles, poly (3,4-ethylenedioxythiophene), isopropyl tri (dodecylbenzenesulfonyl) titanate and dimethyl sulfonic acid are dispersed in an aqueous polyurethane solution with a solid content of 20%-60% to prepare a mixed slurry 2, wherein the mass ratio of antimony tin oxide nanoparticles, poly (3,4-ethylenedioxythiophene), isopropyl tri (dodecylbenzenesulfonyl) titanate, dimethyl sulfonic acid and the aqueous polyurethane solution with a solid content of 20% is 15:20:5:3:400, and then the mixed slurry 2 is brushed onto both sides of the preliminary modified graphite felt, and the brushing amount is 0.1 g / cm 2 , drying at 500°C for 3 min for secondary drying; repeating the steps of “brushing mixed slurry 1-preliminary drying-brushing mixed slurry 2-secondary drying” for 8 times to obtain a multi-layer conductive support layer modified graphite felt; Step S4: Brush polyvinyl alcohol acetal glue onto both sides of the multi-layer conductive support layer modified graphite felt, and then attach graphite paper on both sides thereof to obtain a "graphite paper-multi-layer conductive support layer modified carbon fiber material-graphite paper" structure, wherein the mass ratio of polyvinyl alcohol acetal glue, graphite paper and multi-layer conductive support layer modified graphite felt is 2:0.2:50, and transfer it to a hot press, hot press it at 180°C and 10 MPa for 3 min, and repeat the hot pressing 5 times to obtain a carbon grid-derived multi-layer composite bipolar plate.

[0025] Embodiment 2 This embodiment includes the following steps: Step S1: 8 parts by mass of carbon cloth are washed with acetone, ethanol and deionized water in sequence, and then placed in 200 parts by mass of 1 mol / L copper sulfate etching solution, and 0.2 parts by mass of calcium hydrogen phosphate and 0.5 parts by mass of 1-isopropylpyrrolidine are added thereto for full dispersion, and then the carbon cloth is transferred to an oven and dried at 100°C for 9 h, and the dried carbon cloth is transferred to a tubular furnace and subjected to a staged temperature increase heat treatment under helium protection, that is, firstly heat treated at 400°C for 3 h, and then heated to 950°C for 3 h, and after naturally cooling to room temperature, the obtained carbon cloth is washed with 0.5 mol / L tartaric acid solution and then dried to obtain an etched carbon cloth; Step S2: Disperse conductive carbon black, acrylic resin and magnesium aluminum silicate compound powder in N,N-dimethylacetamide solution to prepare mixed slurry 1, wherein the mass ratio of conductive carbon black, acrylic resin, magnesium aluminum silicate compound powder and N,N-dimethylacetamide solution is 20:5:0.5:80, and apply the mixed slurry 1 to both sides of the etched carbon cloth by brushing, and the brushing amount is 0.2 g / cm 2 and transferred it to a drying oven and dried at 180°C for 15 min for preliminary drying treatment to obtain a preliminary modified carbon cloth; Step S3: Indium tin oxide nanoparticles, polypyrrole, tristearyl titanate isopropyl ester and diamyl sulfate are dispersed in an aqueous polyurethane solution with a solid content of 30% to prepare a mixed slurry 2, wherein the mass ratio of indium tin oxide nanoparticles, polypyrrole, tristearyl titanate isopropyl ester, diamyl sulfate and the aqueous polyurethane solution with a solid content of 30% is 8:40:2:0.5:200, and then the mixed slurry 2 is brushed onto both sides of the preliminary modified carbon cloth, and the brushing amount is 0.2 g / cm 2 , drying at 400°C for 5 min for secondary drying; repeating the steps of “brushing mixed slurry 1-preliminary drying-brushing mixed slurry 2-secondary drying” for 8 times to obtain a multi-layer conductive support layer modified carbon cloth; Step S4: Brush polyvinyl alcohol acetal glue onto both sides of the multi-layer conductive support layer modified carbon cloth, and then attach graphite paper on both sides thereof to obtain a "graphite paper-multi-layer conductive support layer modified carbon fiber material-graphite paper" structure, wherein the mass ratio of polyvinyl alcohol acetal glue, graphite paper and multi-layer conductive support layer modified carbon cloth is 5:1:80, and transfer it to a hot press, hot press it at 160°C and 8 MPa for 6 min, and repeat the hot pressing 7 times to obtain a carbon grid-derived multi-layer composite bipolar plate.

[0026] Embodiment 3 This embodiment includes the following steps: Step S1: 5 parts by mass of carbon paper are washed with acetone, ethanol and deionized water in sequence, and then placed in 300 parts by mass of 0.3 mol / L nickel chloride etching solution, and 0.4 parts by mass of aluminum hydroxide and 1.0 parts by mass of dibenzothiophene are added thereto for full dispersion, and then the carbon paper is transferred to an oven and dried at 80°C for 10 h, and the dried carbon paper is transferred to a tube furnace and subjected to a staged temperature increase heat treatment under nitrogen protection, that is, firstly heat treated at 300°C for 4 h, and then heated to 1000°C for 1 h, and after naturally cooling to room temperature, the obtained carbon paper is washed with 1 mol / L citric acid solution and then dried to obtain etched carbon paper; Step S2: Disperse carbon nanotubes, polyimide resin and coconut diethanolamide in ethyl acetate solution to prepare mixed slurry 1, wherein the mass ratio of carbon nanotubes, polyimide resin, coconut diethanolamide and ethyl acetate solution is 30:2:1.5:100, and apply the mixed slurry 1 to both sides of the etched carbon paper by brushing, and the brushing amount is 0.3 g / cm 2 and transferred it to a drying oven and dried at 160°C for 20 min for preliminary drying treatment to obtain preliminary modified carbon paper; Step S3: Cesium oxide tungsten nanoparticles, poly (3,4-ethylenedioxythiophene), isopropyl tri (dioctyl pyrophosphate) titanate and p-toluene phosphoric acid are dispersed in an aqueous polyurethane solution with a solid content of 40% to prepare a mixed slurry 2, wherein the mass ratio of cesium oxide tungsten nanoparticles, poly (3,4-ethylenedioxythiophene), isopropyl tri (dioctyl pyrophosphate) titanate, p-toluene phosphoric acid and the aqueous polyurethane solution with a solid content of 40% is 10:30:3:1.5:200, and then the mixed slurry 2 is brushed onto both sides of the preliminary modified carbon paper, and the brushing amount is 0.5 g / cm 2 , drying at 300°C for 8 min for secondary drying; repeating the steps of “brushing mixed slurry 1-preliminary drying-brushing mixed slurry 2-secondary drying” for 10 times to obtain a multi-layer conductive support layer modified carbon paper; Step S4: Brush polyvinyl alcohol acetal glue onto both sides of the multi-layer conductive support layer modified carbon paper, and then attach graphite paper on both sides thereof to obtain a "graphite paper-multi-layer conductive support layer modified carbon fiber material-graphite paper" structure, wherein the mass ratio of polyvinyl alcohol acetal glue, graphite paper and multi-layer conductive support layer modified carbon paper is 3:0.5:60, and transfer it to a hot press, hot press it at 140°C and 6 MPa for 8 min, and repeat the hot pressing 3 times to obtain a carbon grid-derived multi-layer composite bipolar plate.

[0027] Embodiment 4 This embodiment includes the following steps: Step S1: After washing 2 parts by mass of carbon felt with acetone, ethanol and deionized water in sequence, the carbon felt is placed in 400 parts by mass of 0.8 mol / L cobalt chloride etching solution, and 0.4 parts by mass of calcium pyrophosphate and 0.8 parts by mass of 2-amino-3-bromothiophene are added thereto for full dispersion, and then the carbon felt is transferred to an oven and dried at 90°C for 9 h, and the dried carbon felt is transferred to a tubular furnace and subjected to staged temperature-raising heat treatment under argon protection, i.e., firstly heat-treated at 300°C for 2 h, and then heated to 900°C for 1 h, and after naturally cooling to room temperature, the obtained carbon felt is washed with 2 mol / L ascorbic acid solution and then dried to obtain an etched carbon felt; Step S2: Disperse carbon nanotubes, epoxy resin and polyethylene glycol in N,N-dimethylacetamide solution to prepare mixed slurry 1, wherein the mass ratio of carbon nanotubes, epoxy resin, polyethylene glycol and N,N-dimethylacetamide solution is 20:4:1.0:120, and apply the mixed slurry 1 to both sides of the etched carbon felt by brushing, and the brushing amount is 0.4 g / cm 2 , and transferred it to a drying oven and dried at 150°C for 20 min for preliminary drying treatment to obtain preliminary modified carbon felt; Step S3: Indium tin oxide nanoparticles, polyaniline, isopropyl trioleyl titanate and polyacrylic acid are dispersed in an aqueous polyurethane solution with a solid content of 25% to prepare a mixed slurry 2, wherein the mass ratio of indium tin oxide nanoparticles, polyaniline, isopropyl trioleyl titanate, polyacrylic acid and the aqueous polyurethane solution with a solid content of 25% is 12:40:4:1:300, and then the mixed slurry 2 is brushed onto both sides of the preliminary modified carbon felt, and the brushing amount is 0.6 g / cm 2 , drying at 350°C for 10 min for secondary drying; repeating the steps of “brushing mixed slurry 1-preliminary drying-brushing mixed slurry 2-secondary drying” for 6 times to obtain a multi-layer conductive support layer modified carbon felt; Step S4: Brush polyvinyl alcohol acetal glue onto both sides of the multi-layer conductive support layer modified carbon felt, and then attach graphite paper on both sides to obtain a "graphite paper-multi-layer conductive support layer modified carbon fiber material-graphite paper" structure, wherein the mass ratio of polyvinyl alcohol acetal glue, graphite paper and multi-layer conductive support layer modified carbon felt is 4:0.8:60, and transfer it to a hot press, hot press it at 200°C and 5 MPa for 5 min, and repeat the hot pressing 7 times to obtain a carbon grid-derived multi-layer composite bipolar plate.

[0028] Embodiment 5 This embodiment includes the following steps: Step S1: 8 parts by mass of carbon paper are washed with acetone, ethanol and deionized water in sequence, and then placed in 400 parts by mass of 1.5 mol / L cobalt acetate etching solution, and 0.6 parts by mass of silicon dioxide and 1.2 parts by mass of 2,3-dimethylbenzofuran are added thereto for full dispersion, and then the carbon paper is transferred to an oven and dried at 110° C. for 8 h, and the dried carbon paper is transferred to a tube furnace and subjected to a staged temperature increase heat treatment under helium protection, that is, firstly heat treated at 400° C. for 3 h, and then heated to 850° C. for 2 h, and after naturally cooling to room temperature, the obtained carbon paper is washed with a 2.5 mol / L nitric acid solution and then dried to obtain an etched carbon paper; Step S2: Disperse graphene, acrylic resin and diethanolamine chloride in ethylene glycol solution to prepare mixed slurry 1, wherein the mass ratio of graphene, acrylic resin, diethanolamine chloride and ethylene glycol solution is 40:2:1.2:140, and apply the mixed slurry 1 to both sides of the etched carbon paper by brushing, and the brushing amount is 0.5 g / cm 2 , and transferred it to a drying oven and dried at 170°C for 15 min for preliminary drying treatment to obtain preliminary modified carbon paper; Step S3: Al-doped zinc oxide nanoparticles, polyaniline, isopropyl tri(dodecylbenzenesulfonyl) titanate and dimethyl sulfonic acid are dispersed in an aqueous polyurethane solution with a solid content of 35% to prepare a mixed slurry 2, wherein the mass ratio of Al-doped zinc oxide nanoparticles, polyaniline, isopropyl tri(dodecylbenzenesulfonyl) titanate, dimethyl sulfonic acid and the aqueous polyurethane solution with a solid content of 35% is 14:25:4:2.5:400, and then the mixed slurry 2 is brushed onto both sides of the preliminary modified carbon paper, and the brushing amount is 0.4 g / cm 2 , drying at 450°C for 3 min for secondary drying; repeating the steps of “brushing mixed slurry 1-preliminary drying-brushing mixed slurry 2-secondary drying” for 8 times to obtain a multi-layer conductive support layer modified carbon paper; Step S4: Brush polyvinyl alcohol acetal glue onto both sides of the multi-layer conductive support layer modified carbon paper, and then attach graphite paper on both sides thereof to obtain a "graphite paper-multi-layer conductive support layer modified carbon fiber material-graphite paper" structure, wherein the mass ratio of polyvinyl alcohol acetal glue, graphite paper and multi-layer conductive support layer modified carbon paper is 5:0.2:80, and transfer it to a hot press, hot press it at 150°C and 7 MPa for 4 min, and repeat the hot pressing 4 times to obtain a carbon grid-derived multi-layer composite bipolar plate.

[0029] Embodiment 6 This embodiment includes the following steps: Step S1: After washing 2 parts by mass of carbon felt with acetone, ethanol and deionized water in sequence, the carbon felt is placed in 400 parts by mass of 2 mol / L ferric nitrate etching solution, and 0.2 parts by mass of calcium hydrogen phosphate and 0.5 parts by mass of 2-amino-3-bromothiophene are added thereto for full dispersion, and then the carbon felt is transferred to an oven and dried at 120°C for 9 h, and the dried carbon felt is transferred to a tubular furnace and subjected to a staged temperature increase heat treatment under nitrogen protection, i.e., firstly heat treated at 500°C for 4 h, and then heated to 1000°C for 3 h, and after naturally cooling to room temperature, the obtained carbon felt is washed with a 3.0 mol / L citric acid solution and then dried to obtain an etched carbon felt; Step S2: Disperse carbon nanotubes, polyimide resin and diethanolamine chloride in ethylene glycol solution to prepare mixed slurry 1, wherein the mass ratio of carbon nanotubes, polyimide resin, diethanolamine chloride and ethylene glycol solution is 30:3:1.0:90, and apply the mixed slurry 1 to both sides of the etched carbon felt by brushing, and the brushing amount is 0.2 g / cm 2 , and transferred it to a drying oven and dried at 190°C for 10 min for preliminary drying treatment to obtain preliminary modified carbon felt; Step S3: Cesium oxide tungsten nanoparticles, polypyrrole, neoalkoxy tris(p-aminophenoxy) titanate and p-toluene phosphoric acid are dispersed in an aqueous polyurethane solution with a solid content of 20% to prepare a mixed slurry 2, wherein the mass ratio of cesium oxide tungsten nanoparticles, polypyrrole, neoalkoxy tris(p-aminophenoxy) titanate, p-toluene phosphoric acid and the aqueous polyurethane solution with a solid content of 20% is 8:20:3:1:300, and then the mixed slurry 2 is brushed onto both sides of the preliminary modified carbon felt, and the brushing amount is 0.4 g / cm 2 , drying at 500°C for 5 min for secondary drying; repeating the steps of “brushing mixed slurry 1-preliminary drying-brushing mixed slurry 2-secondary drying” for 9 times to obtain a multi-layer conductive support layer modified carbon felt; Step S4: Brush polyvinyl alcohol acetal glue onto both sides of the multi-layer conductive support layer modified carbon felt, and then attach graphite paper on both sides thereof to obtain a "graphite paper-multi-layer conductive support layer modified carbon fiber material-graphite paper" structure, wherein the mass ratio of polyvinyl alcohol acetal glue, graphite paper and multi-layer conductive support layer modified carbon felt is 4:0.6:70, and transfer it to a hot press, hot press it at 170°C and 8 MPa for 3 min, and repeat the hot pressing 6 times to obtain a carbon grid-derived multi-layer composite bipolar plate.

[0030] Comparative Example 1 This comparative example has the same steps as Example 1, except that carbon fiber material is replaced by carbon powder, and the following steps are added after step S1: the obtained etching carbon powder is dispersed in a polyvinylidene fluoride dispersion, the obtained mixed solution is poured into a fixed frame of the same thickness as the carbon fiber material used in Example 1, and hot pressed at 150°C for 5 min to obtain a carbon sheet derived from carbon powder; the subsequent steps are the same as Example 1.

[0031] Comparative Example 2 The steps of this comparative example are the same as those of Example 1, except that the etching solution in step S1 is replaced by deionized water, that is, the carbon fiber material is not etched.

[0032] Comparative Example 3 This comparative example has the same steps as Example 1, except that the step S3 of "repeating the steps of 'brushing mixed slurry 1 - preliminary drying - brushing mixed slurry 2 - secondary drying' 8 times" is cancelled, that is, the preliminary modified graphite felt is only brushed with mixed slurry 1 and mixed slurry 2 once each.

[0033] Bipolar plate test method: The conductivity of the bipolar plate was tested using a four-probe resistance meter (ST2258C). Five locations were sampled in each group and the average value was taken.

[0034] With reference to the energy industry standard NB / T 42007-2013 "Test method for bipolar plates for all-vanadium liquid flow batteries", the samples were cut into 10×2 cm size, the initial gauge length of the samples was 50 mm, and the test was carried out by stretching at a speed of 1 mm / min. The bending strength of the samples was determined by a three-point bending test using a mechanical testing machine, and the bending strength of the composite bipolar plate was measured at a loading speed of 1 mm / min. Five samples were tested in each group and the average value was taken.

[0035] The embodiment and the comparative example were assembled into a stack for testing at a current density of 120 mA / cm 2 , record the voltage efficiency, energy efficiency and energy efficiency after 300 cycles. The test results are shown in Table 1: Table 1 Summary of bipolar plate and battery test results

[0036] As can be seen from Table 1, by comparing Examples 1-6 with Comparative Example 1, it can be seen that when carbon powder is used instead of the etched carbon fiber material, the prepared bipolar plate has a higher conductivity and a lower tensile and flexural strength. This may be because the carbon powder is a loose particle structure, and factors such as particle size, shape and distribution are uneven and different, which makes it impossible to build an effective conductive network, and the subsequent problems of carbon powder agglomeration and uneven dispersion also make it impossible to effectively improve its conductivity, thereby resulting in a decrease in the conductivity of the composite bipolar plate, indicating that the high neatness and uniformity of the carbon fiber material structure provide a good network structure for electron conduction, which is beneficial to the improvement of the conductivity of the bipolar plate, and its interwoven fiber substrate also provides good durability and stability for the composite bipolar plate, enhances its mechanical strength, and improves tensile and flexural strength; It can be seen from Examples 1-6 and Comparative Example 2 that when the carbon fiber material is not etched, the prepared The electrical conductivity of the bipolar plate is lower than that of the bipolar plate prepared by etching carbon fiber material, and the tensile strength and flexural strength are reduced. This is because the etching treatment of graphite felt can effectively improve the surface roughness and active surface area of ​​the carbon fiber material, enhance the mechanical interlocking effect between the carbon fiber material and the conductive filler and binder, enhance the bonding strength between the two, form a stronger interface bonding force, and improve the mechanical strength, stability and conductivity of the composite bipolar plate; comparing Examples 1-6 with Comparative Example 3, when the conductive support layer slurry is only applied once, the resulting composite bipolar plate has lower electrical conductivity and smaller tensile and flexural strength, which may be attributed to the additional introduction of the conductive support layer slurry, which is beneficial to the construction and improvement of the carbon grid, strengthens the surface interface electronic conduction of the composite bipolar plate, and thus enhances its conductivity, and the introduction of multiple support layers can also improve the structural stability inside the bipolar plate, thereby enhancing its mechanical strength and improving its stability in the application of all-vanadium liquid flow batteries.

Claims

1. A method for preparing a multilayer composite bipolar plate derived from a carbon grid for a vanadium battery, characterized in that: The main steps include: Step S1: After washing 2-8 parts by mass of carbon fiber material with acetone, ethanol and deionized water in sequence, placing it in 200-400 parts by mass of etching solution and adding 0.2-0.6 parts by mass of reinforcing agent and 0.5-1.2 parts by mass of stabilizer thereto, the carbon fiber material is fully dispersed, and then the carbon fiber material is transferred to an oven for drying treatment, and the dried carbon fiber material is transferred to a tubular furnace, and subjected to staged temperature increase heat treatment under the protection of an inert gas, and after naturally cooling to room temperature, the obtained carbon fiber material is cleaned with a chemical cleaning agent and then dried to obtain an etched carbon fiber material; Step S2: Disperse the conductive filler, binder and excipient in an organic solvent to prepare a mixed slurry 1, and apply the mixed slurry 1 to both sides of the etched carbon fiber material with a brushing amount of 0.2-0.5 g / cm 2 and transferring it to a drying oven for preliminary drying treatment to obtain a preliminary modified carbon fiber material; Step S3: Disperse oxide nanoparticles, conductive polymer, phthalate coupling agent and dispersant in an aqueous polyurethane solution with a solid content of 20%-40% to prepare a mixed slurry 2, and then apply the mixed slurry 2 to both sides of the preliminary modified carbon fiber material with a brushing amount of 0.1-0.6 g / cm 2 , and perform secondary drying treatment; repeat the "brushing mixed slurry 1-preliminary drying-brushing mixed slurry 2-secondary drying" step 6-10 times to obtain a multi-layer conductive support layer modified carbon fiber material; Step S4: Brush polyvinyl alcohol acetal glue onto both sides of the multi-layer conductive support layer modified carbon fiber material, and then attach graphite paper on both sides to obtain a "graphite paper-multi-layer conductive support layer modified carbon fiber material-graphite paper" structure, transfer it to a hot press, set the temperature and pressure, and perform hot pressing to obtain a carbon grid-derived multi-layer composite bipolar plate.

2. The method for preparing a multi-layer composite bipolar plate derived from a carbon grid for a vanadium battery according to claim 1, characterized in that: In step S1, the carbon fiber material is one of carbon paper, carbon cloth, carbon felt and graphite felt; the etching solution is one of chloride solution, sulfate solution, nitrate solution and acetate solution of nickel, copper, cobalt and iron, as an illustrative example, it can be one of nickel chloride solution, copper sulfate solution, ferric nitrate solution and cobalt acetate solution, and the molar concentration of the etching solution is 0.3-2 mol / L; the enhancer is one of calcium hydrogen phosphate, calcium carbonate, calcium pyrophosphate, aluminum hydroxide and silicon dioxide; the stabilizer is one of dibenzothiophene, 1-isopropylpyrrolidine, octahydroisobenzofuran, 2,3-dimethylbenzofuran and 2-amino-3-bromothiophene.

3. The method for preparing a multi-layer composite bipolar plate derived from a carbon grid for a vanadium battery according to claim 1, characterized in that: In step S1, the drying heat treatment temperature is 80-120°C, the time is 8-10 h, and the inert gas is one of nitrogen, argon and helium; the staged heating heat treatment process is: first heat treatment at 300-500°C for 2-4 h, and then heat treatment at 850-1000°C for 1-3 h.

4. The method for preparing a multi-layer composite bipolar plate derived from a carbon grid for a vanadium battery according to claim 1, characterized in that: In step S1, the chemical cleaning agent is one of citric acid solution, sulfuric acid solution, tartaric acid solution, ascorbic acid and nitric acid solution, and the concentration of the chemical cleaning agent is 0.5-3 mol / L.

5. The method for preparing a multi-layer composite bipolar plate derived from a carbon grid for a vanadium battery according to claim 1, characterized in that: In step S2, the conductive filler is one of conductive carbon black, graphene and carbon nanotubes; the binder is one of epoxy resin, polyimide resin, polyurethane resin and acrylic resin; the excipient is one of magnesium aluminum silicate compound powder, diethanolamine chloride, polyethylene glycol and coconut diethanolamide; the organic solvent is one of N,N-dimethylacetamide solution, xylene solution, ethyl acetate solution and ethylene glycol solution; the mass ratio of the conductive filler, the binder, the excipient and the organic solvent is (20-40): (2-5): (0.5-1.5): (80-150).

6. The method for preparing a multi-layer composite bipolar plate derived from a carbon grid for a vanadium battery according to claim 1, characterized in that: The temperature of the preliminary drying treatment in step S2 is 150-200°C and the time is 10-20 min.

7. The method for preparing a multi-layer composite bipolar plate derived from a carbon grid for a vanadium battery according to claim 1, characterized in that: In step S3, the oxide nanoparticles are one of indium tin oxide, antimony tin oxide, cesium tungsten oxide and aluminum-doped zinc oxide; the conductive polymer is one of polyaniline, polypyrrole and poly (3,4-ethylenedioxythiophene); the phthalate coupling agent is one of isopropyl trioleyl titanate, isopropyl tri (dodecylbenzenesulfonyl) titanate, tristearyl titanate isopropyl ester, isopropyl tri (dioctyl pyrophosphate) titanate and neoalkoxy tri (p-aminophenoxy) titanate; the dispersant is one of polyacrylic acid, dimethyl sulfonic acid, p-toluene phosphoric acid and diamyl sulfate; the mass ratio of the oxide nanoparticles, the conductive polymer, the phthalate coupling agent, the dispersant and the aqueous polyurethane solution with a solid content of 20%-40% is (8-15): (20-40): (2-5): (0.5-3): (200-400).

8. The method for preparing a multi-layer composite bipolar plate derived from a carbon grid for a vanadium battery according to claim 1, characterized in that: The secondary drying treatment temperature in step S3 is 300-500° C. and the time is 3-10 min.

9. The method for preparing a multi-layer composite bipolar plate derived from a carbon grid for a vanadium battery according to claim 1, characterized in that: In step S4, the mass ratio of polyvinyl alcohol acetal glue, graphite paper and multi-layer conductive support layer modified carbon fiber material is (2-5): (0.2-1): (50-80), the hot press temperature is set to 140-200°C, the pressure is set to 5-10 MPa, the hot pressing time is 3-8min, and the number of hot pressing times is 3-7 times.

10. A multi-layer composite bipolar plate derived from a carbon grid for a vanadium battery, prepared by the method for preparing a multi-layer composite bipolar plate derived from a carbon grid for a vanadium battery according to claims 1-9.

Citation Information

Patent Citations

  • Proton exchange membrane fuel cell bipolar plate and preparation method therefor

    CN107611458A

  • Fuel cell stainless steel bipolar plate preparation and surface modification method

    CN110289428A

  • All-vanadium redox flow battery bipolar plate and preparation method thereof

    CN110676479A

  • Method for preparing vanadium battery integrated electrode from fluoroplastic

    CN111092232A

  • Flexible ultrathin graphite bipolar plate and preparation method thereof

    CN113224339A

Cited By

  • Composite metal bipolar plate of fuel cell and preparation method of composite metal bipolar plate

    CN119843336A

  • Multi-component composite bipolar plate for vanadium redox flow battery and preparation method of multi-component composite bipolar plate

    CN120999032A

  • High-conductivity carbon fiber material, preparation method thereof and application of high-conductivity carbon fiber material in bipolar plate of flow battery

    CN121023808A